Trends in road injury hospitalisation rates for Aboriginal and non-Aboriginal people in Western Australia, 1971–97. Issue 3 (1st September 2002) - Cercarelli, L R; Knuiman, M W
Abstract : Objective: To examine trends in road injury hospitalisation rates for Aboriginal and non-Aboriginal people in Western Australia. Methods: Data from the Western Australian Hospital Morbidity Data System for the years between 1971 and 1997 were analysed. Poisson regression models were fitted to determine whether the trends were significant. Results: The rate of hospitalisation due to road injury for Aboriginal people (719.1 per 100 000 population per year) over the time period examined was almost twice as high as that for non-Aboriginal people (363.4 per 100 000 population per year). Overall, the results showed that while hospitalisations from road injury involving non-Aboriginal people have been decreasing by 6.7% per three year period since 1971, the rates of hospitalisation for Aboriginal people have been increasing by 2.6% per three year period. Both of these trends were statistically significant. The alarming increasing trend observed for Aboriginal people was more pronounced in males, those aged 0–14 years and over 45 years, and for those living in rural areas. Conclusions: As the rates of road injury for Aboriginal people are higher than for non-Aboriginal people, and are also following an increasing trend, road safety issues involving Aboriginal people need to be addressed urgently by health and transport authorities.